Views on online self-help programmes from people with eating disorders and their carers in UK. (7th July 2021) - Yim, See Heng; Spencer, Lucy; Gordon, Gemma; Allen, Karina L; Musiat, Peter; Schmidt, Ulrike
Abstract: Background: Digitalizing the healthcare system has been declared a priority by the UK government. People with eating disorders (EDs), especially those with bulimia nervosa (BN) or binge eating disorder (BED), and ED carers may benefit from online self-help programmes, due to the shame and stigma associated with EDs and barriers in accessing treatment, skills-training or support. Qualitative studies are needed to explore stakeholders' needs, attitudes to and views about online self-help, to optimize intervention design and delivery. Methods: Focus groups and telephone interviews were conducted with people with BN or BED, and carers of people with anorexia nervosa, between March and September 2018 in the UK. Results: People with EDs and carers perceived online self-help positively in the context of barriers to seeking and accessing treatment and support, despite some seeing it as inferior to face-to-face support. Most reported little experience with online interventions. Participants thought the disadvantages of online interventions could be overcome by reminders, progress summaries, regular engagement and engaging with peers. Receiving guidance was seen as an important functionality in the intervention by people with EDs. Conclusions: People with EDs and their carers are aware of the potential benefits of online self-help despite having little experience with this form of intervention. A stepped-care approach that utilizes technology-based interventions as a first step and makes such interventions available directly to the consumer may fit the attitudes and needs of stakeholders. The study provides a foundation for future research on design and delivery of ED online self-help.